(3GdeNJGQ ef GdCUeYjGJs - (3GdGUeYj , YHO Gdedc Hf bQjH Hf Ydj Hf GUeY GdHGgdj, CHh SYjO,J (B216 (3g` s
(3ChdgG (B:s
(3hbGd GdCShO Hf jYVQ fGe GdnNdoqj heG CMS oQbGOj hGdge oeMJVQ dOj hSGOj GdNdqj GdaGQZ ef Gdgehe s
(3BNQgG (B:s
(3ef bUjOI dYeQh Hf eYO jcQH pcdG SjOjce bO CPbfGg WYfg hYGdL GfHhHkG ef GdNW jGHSkG Cj QeMkG NWjkG Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdNW eged GdfbW CMjGfkGs
(3Hjf GdCHjGJ bdjd ef GdeYGfj hGdTQhMs
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI hHBNQgG bQGAI JeJ aj (B613(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs